The Interplay of the Technique of Cinematography in Contemporary Iraqi Poetry: Saadi Yusuf as A Case Study (An Analytical Study in Selected Models) - Burhan, Dalal; Toklubok, Pabiyah (Dirasat: Human and Social Sciences, 2020)
The Interplay of the Technique of Cinematography in Contemporary Iraqi Poetry by Saadi Yusuf is one of the contemporary studies that have not received full attention in terms of study and analysis. A study like this is meant to shed light on the impact of new aesthetic arts such as cinema on the development of the production of contemporary poetic structure. This study attempts to bridge the gap in literature by revealing the role of the technique of cinematography in the evolution of artistic structures. This study aims at clarifying the relationship between the art of contemporary Iraqi poetry and the art of cinema, highlighting the most important techniques for the interplay of the cinematic shot in the poem, and identifying the types of cinematography used by the poet in his collection of poems (the three rivers). To achieve these objectives, the analytical descriptive method was used to analyze the poems in terms of employing the technique of Cinematography in the poet’s collection of poems, based on the use of cinematic style in the contemporary Iraqi poem. It has also been analyzed in terms of the interplay between the art of poetry and the art of cinema. The findings showed that the use of the technique and its types (near-range, medium-range, general) has made his poems more innovative and open in terms of freeing such poems from weakness of meaning, language complexity, and contradictory poetic meanings.